Lipid modification to improve cryotolerance of gametes, embryos and larvae and its potential application in aquaculture species: a review - Zhu, Xiaochen; Miller-Ezzy, Penny; Zhao, Yingying; Qin, Jianguang; Tang, Youhong; Liu, Yibing; Li, Xiaoxu (Frontiers in Marine Science, 2023)
Cryopreservation is a technique to maintain biological materials’ physiological and genetic stability at an ultralow temperature. For commercially important livestock or aquatic species, gamete and embryo cryopreservation could play a significant role in breeding programs and commercial production. For example, it could help overcome key problems such as asynchronous maturation and an unbalanced sex ratio. However, the physiochemical stresses imposed by cryopreservation can negatively affect gametes and embryos, leading to a poor survival rate. Recent studies on cryoinjury have demonstrated that the cryosensitivity of lipids is one of the key causes of cryodamage in mammalians, as lipid compositions in membranes of gametes and embryos are closely related to their cryoresistance. In addition, the cryotolerance of gametes and embryos in some mammalian species has been improved by lipid modification. However, studies on the role of lipids in the cryopreservation of gametes, embryos, and larvae are rare in fish and shellfish. Therefore, this review focuses on recent methodological advances to improve cryotolerance by lipid modification, including lipid application or manipulation in human and livestock sperm, oocytes, and embryos, and how these novel approaches could improve cryopreservation techniques in aquatic species, especially for oocytes and embryos.